2009
DOI: 10.1007/s00216-009-3058-4
|View full text |Cite
|
Sign up to set email alerts
|

The study of bronze statuettes with the help of neutron-imaging techniques

Abstract: Until recently fabrication techniques of Renaissance bronzes have been studied only with the naked eye, microscopically, videoscopically and with X-radiography. These techniques provide information on production techniques, yet much important detail remains unclear. As part of an interdisciplinary study of Renaissance bronzes undertaken by the Rijksmuseum Amsterdam, neutron-imaging techniques have been applied with the aim of obtaining a better understanding of bronze workmanship during the Renaissance period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…If eventually are visible any kind of crack(s) on obtained X-ray film, as here, the registered indications may however serve for further engineering analyze of a production method and kind(s) of faults through the entire body, even when the artistic part is an object of observation or investigation [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. But, irregularities visible from Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If eventually are visible any kind of crack(s) on obtained X-ray film, as here, the registered indications may however serve for further engineering analyze of a production method and kind(s) of faults through the entire body, even when the artistic part is an object of observation or investigation [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. But, irregularities visible from Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that, when is used X-ray diagnostic methods in conjunction with art, historical and technical knowledge of artistic works than will impact on change the understanding of art objects given by curators based on stylistic features [1][2][3]. Although a few museums have been examined their sculptures, in more or less systematic way, still exists the relatively small number of results of X-ray diagnostic methods of sculpture collections.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, attenuation of X-rays rises with increasing atomic number and density while with neutrons there is no direct relationship between atomic weight and transmission [14]. Regarding metals of ancient interest, the attenuation of neutrons in different elements follows the order Au N Ag N Fe N Cu N Pb N Sn (with neutrons being more attenuated in Au than Sn) while for X-rays is Pb N Au N Sn N Ag N Cu N Fe.…”
Section: Introductionmentioning
confidence: 98%
“…Although copper and tin have relatively short half-lives (12.7 h and 27 h respectively), other elements that can be present in small concentrations in copper or bronze can stay activated for many days (e.g. Zn 244 days, Co 5.2 years, Ag 250 days) [14], preventing the artifacts to be handled shortly after the neutron analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Neutron imaging [1][2][3][4] and neutron diffraction [5][6][7] have been demonstrated to be important tools in the study of archaeological artefacts because they allow morphological and compositional analysis of the objects in a completely nondestructive way. The combination of imaging and compositional analyses using neutrons, as well as complementary techniques, have been exploited in a few studies.…”
Section: Introductionmentioning
confidence: 99%